Acute Exposure to a Precursor of Advanced Glycation End Products Induces a Dual Effect on the Rat Pancreatic Islet Function - Ghada Elmhiri; Luiz Felipe Barella; Didier Vieau; Sylvaine Camous; Paulo C. F. Mathias; Latifa Abdennebi-Najar (International Journal of Endocrinology)
Aim. Chronic diseases are the leading cause of death worldwide. Advanced glycation end products, known as AGEs, are a major risk factor for diabetes onset and maintenance. Methylglyoxal (MG), a highly reactive metabolite of glucose, is a precursor for the generation of endogenous AGEs. Methods. In this current study we incubated in vitro pancreatic islets from adult rats in absence or presence of MG (10 μmol/l) with different concentrations of glucose and different metabolic components (acetylcholine, epinephrine, potassium, forskolin, and leucine). Results. Different effects of MG on insulin secretion were evidenced. In basal glucose stimulation (5.6 mM), MG induced a significant (P<0.05) increase of insulin secretion. By contrast, in higher glucose concentrations (8.3 mM and 16.7 mM), MG significantly inhibited insulin secretion (P<0.05). In the presence of potassium, forskolin, and epinephrine, MG enhanced insulin secretion (P<0.05), while when it was incubated with acetylcholine and leucine, MG resulted in a decrease of insulin secretion (P<0.05). Conclusion. We suggest that MG modulates the secretion activity of beta-cell depending on its level of stimulation by other metabolic factors. These results provide insights on a dual acute effect of MG on the pancreatic cells.